Legal Certainty Regarding Covernotes Issued by Notaries as Temporary Guarantees for Creditors in Banking Practices - Dwi Arepa, Nola; Shallman, Shallman; Arpangi, Arpangi (TABELLIUS: Journal of Law, 2026)
This study aims to comprehensively analyze the legal status of covernotes issued by Notaries in banking practices and the forms of legal liability in the event of negligence that results in losses for creditors. This issue is relevant because in the practice of credit disbursement, especially loans secured by mortgage rights, covernotes are often used as administrative basis before the binding and registration process of the collateral is fully completed. However, normatively, there are no explicit regulations regarding covernotes in the provisions of Law Number 2 of 2014 concerning the Position of Notaries or in the legal regime of material collateral. This research uses a normative juridical method with a statutory and conceptual approach, analyzed qualitatively through a literature review of primary, secondary, and tertiary legal materials. The analysis was conducted by examining the principle of legal certainty, the principle of prudence in banking, and the theory of legal responsibility. The research results show that the covernote is not an authentic deed as defined in the Notary Law, because it does not fulfill the formal requirements as a deed made by or before a public official in a form prescribed by law. The covernote is also not an agreement that creates a new legal relationship, but rather an administrative statement that essentially only contains information regarding an ongoing process. Therefore, the covernote does not have perfect evidentiary power or executorial power like a mortgage certificate. However, in banking practice, covernotes are often used as the basis for credit disbursement due to efficiency and business needs. This situation has the potential to create legal uncertainty if there is a failure to complete the binding or registration of collateral. In the event of losses due to a notary's negligence, legal liability can be sought in the form of civil liability based on breach of contract or unlawful acts, administrative liability through the notary's job oversight mechanism, and ethical liability in accordance with the professional code of ethics. Therefore, it is necessary to clarify the limitations of the function and position of covernotes to ensure legal certainty and balanced protection for all parties in banking practice.